2013
DOI: 10.1038/bmt.2013.154
|View full text |Cite
|
Sign up to set email alerts
|

Combination of a haploidentical SCT with an unrelated cord blood unit: a single-arm prospective study

Abstract: We conducted a single-arm prospective study in 50 patients who received the combination of an haploidentical stem cell graft and an unrelated umbilical cord blood unit for the treatment of hematological malignancies. The median time for neutrophil engraftment was 13 days (11-20 days), and for platelets was 15 days (11-180 days). All surviving patients attained complete haploidentical engraftment except three patients who presented a mixed engraftment with increasing cord blood and decreasing haplo mismatch chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
42
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 46 publications
6
42
2
Order By: Relevance
“…13 Recent data have shown that haploidentical stem cell transplants with support from cord blood, which contains a subset of regulatory T-cell and mesenchymal stromal cells, could significantly reduce the incidences of severe acute GVHD in the treatment of hematological malignancies. 6,14 In this boy, we used haploidentical transplantation with a coinfusion of cord blood to treat CCALD. After transplantation, there was rapid and sustained neutrophil and platelet engraftment, without severe acute GVHD; he showed neurological stability for 6 months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Recent data have shown that haploidentical stem cell transplants with support from cord blood, which contains a subset of regulatory T-cell and mesenchymal stromal cells, could significantly reduce the incidences of severe acute GVHD in the treatment of hematological malignancies. 6,14 In this boy, we used haploidentical transplantation with a coinfusion of cord blood to treat CCALD. After transplantation, there was rapid and sustained neutrophil and platelet engraftment, without severe acute GVHD; he showed neurological stability for 6 months.…”
Section: Discussionmentioning
confidence: 99%
“…5 To avoid this, several studies have adopted haploidentical stem cell transplants with umbilical cord blood infusion to enhance immune reconstitution and prevent GVHD for hematological malignancies. 6 However, very little is known about its use for CCALD patients. This is the first report of a CCALD patient who successfully received a haploidentical stem cell transplant combined with an unrelated umbilical cord blood unit.…”
Section: Introductionmentioning
confidence: 99%
“…58 An alternative strategy has involved infusing both an UCB unit and a haplo allograft. 5961 Although this approach resulted in rapid engraftment, two of the three published studies still showed high NRM of 28% and 35%. Overall, low chronic GVHD and potentially lower relapse with UCBT have made it a promising transplantation platform to continue to refine.…”
Section: Umbilical Cord Bloodmentioning
confidence: 99%
“…This approach has also not reliably demonstrated a reduction in time to donor engraftment, with reported median neutrophil and platelet engraftment times ranging widely between 12-32 days and 41-105 days, respectively [41]. Current clinical trials are exploring new strategies such as co-infusion of haplo-identical CD34 stem cells in the setting of a conventional single or double cord blood unit transplantation (DCBT) [42] to achieve initial rapid neutrophil engraftment from the haploidentical cells, which eventually get rejected while the CB graft gradually takes over hematopoiesis.…”
Section: Enhancing Cord Blood Transplantsmentioning
confidence: 99%